Hundred-year changes in the avifauna of the Valley of Mexico, Distrito Federal, Mexico - A. Townsend Peterson (Huitzil. Revista Mexicana de Ornitología, 2006)
Species lists were compiled for the Valley of Mexico from the nineteenth century and from 1950-present. Of a total of 401species, 228 were documented to be present in both time periods, 111 were detected only in recent observations, and 62were detected only in the nineteenth century. Composition of species detected in one time period and not the other wassimilar (aquatic, montane, migratory); however a number of records for the nineteenth century indicate the presence of anaquatic avifauna associated with large lakes. Indeed, 14 species in this aquatic avifauna are otherwise absent or poorlyrepresented in interior Mexico, suggesting that the Valley of Mexico was a unique natural area. Introduced exotic specieswere numerous in both time periods, with a surprising number of failed opportunities for establishment of populations